STUDENTS AND LECTURERS’ PERSPECTIVES ON THE IMPORTANCE OF MOTIVATIONAL STRATEGY IN ENGLISH LANGUAGE TEACHING AND LEARNING PROCESS - Redi Pudyanti, A.A.A.; Nitiasih, P.K.; Suarnajaya, I W. (Universitas Pendidikan Ganesha, 2013)
Abstrak Artikel ini mengenai pandangan mahasiswa dan dosen terhadap pentingnya strategi motivasi pada proses pembelajaran Bahasa Inggris, yang bertujuan untuk: (1) mengetahui pandangan mahasiswa tentang pentingnya strategi motivasi tertentu dalam proses belajar-mengajar bahasa Inggris; (2) pandangan dosen tentang pentingnya strategi motivasi tertentu dalam proses belajar-mengajar bahasa Inggris; (3) membandingkan pandangan mahasiswa dan dosen tentang pentingnya strategi motivasi tertentu dalam proses belajar-mengajar bahasa Inggris; (4) mengamati penerapan strategi motivasi yang diterapkan dosen dalam proses belajar-mengajar bahasa Inggris.tentang pentingnya strategi motivasi tertentu dalam proses belajar-mengajar bahasa Inggris. Penelitian ini didasari oleh teori strategi memotivasi Dornyei (2001). Metode yang digunakan dalam penelitian ini adalah explanatory mixed method design. Berdasarkan analisis data kuantitatif, yang kemudian dikelompokkan berdarkan rumus Nurkacana?s (1992), hasil penelitian ini menunjukkan bahwa: dimensi menciptakan kondisi motivasi dasar dipandang penting oleh mahasiswa (cI=4.22) dan dosen (cI=4.43); dimensi membangkitkan motivasi awal dipandang penting oleh mahasiswa (cII=3.82) dan sangat penting oleh dosen (cII = 4.70); dimensi memelihara dan menjaga motivasi dipandang penting oleh mahasiswa (cIII=3.99) dan sangat penting oleh dosen (cIII=4.54), dimensi dan strategi evaluasi yang positif dipandang penting baik oleh mahasiswa (cIV=3.61) maupun dosen (cIV=4.40). Namun terdapat beberapa perbedaan pendapat mengenai penerapan strategi motivasi tertentu dalam masing-masing dimensi. Didalam penerapannya, dosen menerapkan sebagian besar strategi memotivasi pada keempat dimensi yang disarankan Dornyei, dan terdapat beberapa strategi yang belum diterapkan oleh para dosen. Kata Kunci: strategi motivasi, pembelajaran bahasa Inggris, pembelajar dewasa, pandangan mahasiswa, pandangan dosen. Abstract This article is concerned with the study on students and lecturers? perspectives on the importance of motivational strategy in English language teaching and learning process, which aims at investigating: (1) Students? perspectives on the importance of motivational strategies helping them in the foreign language teaching and learning process; (2) lecturers? perspectives on the importance of motivational strategies that should be applied in foreign language teaching and learning process; (3) The comparison between students and lecturers? perspectives on the importance of motivational strategies in foreign language teaching and learning process; (4) Lecturers? implementation of motivational strategies in the foreign language teaching and learning process. The motivational strategies used were based on Dornyei?s theory (Dornyei, 2001), that consists of four important dimensions: creating basic motivational conditions, generating initial motivation, maintaining and protecting motivation, and creating positive evaluation. The data of this study were collected by means of some methods of data collections, such as: questionnaires, observation, and interview. There were two kinds of questionnaires used in this study: questionnaires for students and questionnaires for lecturers, which were adapted and have been translated from Dornyei?s (2001) theory on motivational strategies. Based on the quantitative data analysis, which was further categorized using Nurkacana?s formula (1992), the result of this study revealed that: the dimension of creating basic motivational conditions is considered important for both students (cI=4.22) and lecturers (cI=4.43); the dimension of generating initial motivation is considered important for students (cII=3.82) and very important for lecturers (cII=4.70); the dimension of maintaining and protecting motivation is considered important for students (cIII=3.99) and very important for lecturers (cIII=4.54), and creating positive evaluation is considered important for both students (cIV=3.61) and lecturers (cIV=4.40). Moreover, there are some strategies proposed by Dornyei (2001) that were not applied by the lecturers. Keywords: motivational strategy, English language learning, adult learner, students? perspectives, lecturers? perspectives.